Teaching And Learning Reading Comprehension through Close Reading: Insights from First-Semester EFL Students - Septa Aryanika (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
Reading comprehension is a fundamental skill in English language learning; however, many non-English-major students encounter difficulties in understanding academic texts. This study investigated the implementation of the Close Reading strategy in teaching reading comprehension to first-semester non-English-major students at UIN Raden Intan Lampung and explored students’ perceptions of the strategy. Using a qualitative case study design, data were collected through classroom observations and semi-structured interviews and analyzed thematically. The findings revealed that the implementation of Close Reading involved five stages: text selection, independent reading, lecturer modeling, collaborative discussion, and text-based questioning. The strategy helped students activate prior knowledge, apply strategic reading behaviors, engage in collaborative meaning-making, and support their answers with textual evidence. Students perceived the strategy positively because it enabled them to understand texts more systematically and critically. Nevertheless, challenges related to vocabulary limitations, inferential comprehension, translation dependence, and confidence were still observed. Overall, the study demonstrates that Close Reading provides an effective instructional framework for improving reading comprehension and fostering critical reading practices among EFL learners. These findings suggest that the strategy can be integrated into reading instruction for non-English-major students to support deeper engagement with academic texts.